2019
DOI: 10.13189/ujer.2019.071915
|View full text |Cite
|
Sign up to set email alerts
|

Generic Green Skills in Teaching and Learning: Meaning and Implementation

Abstract: The burgeoning of green economies has sparked the development of green skills, primarily to fulfil the demanding requirement of green-collar employees. Human resources equipped with specific generic green skills will become a catalyst to penetrate the green job market. On the principle that skills can be shaped through education and training, a qualitative study was conducted using in-depth interviews with senior academics from the School of Education, of a local university in southern Peninsular Malaysia. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
(1 reference statement)
0
10
0
Order By: Relevance
“…To record students' attendance in the lecture room, QR codes were used extensively. This indicates that the ingenuity of students in the use of smartphones showed that digital skill is another complement to green skills (Hamid et al, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…To record students' attendance in the lecture room, QR codes were used extensively. This indicates that the ingenuity of students in the use of smartphones showed that digital skill is another complement to green skills (Hamid et al, 2019).…”
Section: Discussionmentioning
confidence: 90%
“…Achieving sustainability will necessitate training processes at various levels as well as teaching programs in green economy and sustainability (Abd et al, 2019). Institutions need to include green economy leaning in every degree and educational program taught.…”
Section: Discussionmentioning
confidence: 99%
“…This green skill is important for TVET educators to accomplish the need of society and future nation capitals . Hamid et al (2019) in a recent study have encouraged generic green skills in teaching and learning for upcoming manpower employability, especially for the green job labor market. To be a competent TVET educator, high awareness and practice of generic green skills should always be implemented as such the practice of e-learning, digital technology, electricity-saving, smartphone usage, and application of ICT in teaching material.…”
Section: Issue Of Greening Tvetmentioning
confidence: 99%
“…The greening TVET is a skill that combines harmoniously elements of knowledge, technical and non-technical skills as well as attitudes towards sustainable human resources. Thus, a combination of green education and training is important for TVET educators to cultivate a future workforce with the knowledge of ecologically friendly and sustainable technologies (Hamid et al, 2019).…”
Section: Issue Of Greening Tvetmentioning
confidence: 99%